New data on brown coal occurrences in the Yamutarida and Dyuntaturku-yamu river basin in the northern part of the Yenisei-khatanga trough - A. N. Zhuravlév; I. E. Stukalova (Известия высших учебных заведений: Геология и разведка)
Background. New information was obtained on brown coal occurrences in the northern part of the Yenisei-Khatanga trough (Lake Taimyr area). This region continues to attract the attention of geologists and oil producers due to its established oil and gas potential.Aim. To study the lithological features of rocks and material-petrographic composition of coals from a new promising area of the Yenisei-Khatanga trough in northern Russia.Materials and methods. A set of geological, lithological, and petrographic research methods was used to study a series of samples of coals and host rocks. Measurements were carried out on a QDI-302 Craic Spectrophotometer microscope with a 50× objective lens according to the standard methodology ISO 7404-5 in reflected polarised light using a Spinel standard (Ro = 0.426%) in oil immersion. X-ray fluorescence analysis was performed using a Respect device with an energy dispersive spectrometer without vacuum, having an X-ray tube with a silver anode (registration of elements only from K to U). Anode voltage — 30 kV. Current — 0.3 mA. Exposure time (τ) — 300 s. Y axis — intensity of characteristic lines, rel. unitsResults. The lithological features of the studied samples were elucidated, and the material-petrographic composition of the coals was studied. In the spore-pollen assemblage from the studied deposits, the dominant associations were determined by the predominance of two-bag pollen of Disaccites (Pinaceae) conifers. On this basis, the age of the Begichevskaya Formation rocks was established as belonging to the Albian and Cenomanian stages of the Lower-Middle Cretaceous.Conclusion. The degree of variability of coals was estimated; their grades (technological groups) and the trace element composition of ash were determined. The reflection values of vitrinites were measured in order to clarify the stage of changes in brown coals and obtain the quantitative characteristics of their quality. The reflection values of vitrinites (Ro) are from 0.32 to 0.52%, which corresponds to the stages of brown coal changes, technological groups 1B—3B.